Description of new species of leaf miners (Diptera Agromyzidae) associated with leguminous host described from northern India - Thapa, Ram Bahadur (Nepalese Journal of Biosciences, 2013)
A total of 28 species of agromyzid flies belonging to 7 genera have been reared and described on 34 different leguminous host -plants from Pantnagar, Nainital, Northern India. 13 agromyzid flies have been described as new species viz., Japanagromyza species nova (sp.n.) ex leaves of Pueraria phaseoloides (Roxb.) Benth; Liriomyza sp.n. ex leaves of Vicia sativa Linn.; Liriomyza sp.n. ex leaves of Vicia faba Linn.; Malanagromyza sp.n. ex stems of Cassia sp.; Melanagromyza sp.n. ex stems of Pisum sativum Linn. Melanagromyza sp.n. ex stems of Trifolium pratense Linn.; Melanagromyza sp.n. ex stems of Vicia faba Linn.; Ophiomyia sp.n. ex stems of Pueraria Phaseoloides (Roxb.) Benth; Ophiomyia sp.n. ex stems of Sesbania aculeata Pers.; Ophiomyiz sp.n. ex stem of Vigna mungo (Linn.) Heeper and Ophiomyia sp.n. ex stems of Vigna mungo (Linn.) Heeper. Large numbers of host plants have been recorded as new host for various agromyzid species. More than one thousand male genitalia slides have been prepared for this study. Variations in morphology and genitalia characters have also been illustrated within the species. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7474 Nepalese Journal of Biosciences 1: 66-82 (2011)